The Properties of Neutron Halo Structure for 17B and 22N nuclei - Yaseen A Alsajjad, Alzahraa; N Abdullah, Ahmed (Al-Nahrain Journal of Science, 2019)
The radial wave functions of the Harmonic Oscillator and Woods-Saxon potentials within the three-body [two-body] model of    have been used to study some of the basic structural features such as the ground state proton, neutron and matter densities, the associated root mean square (rms) radii and elastic form factors of neutron-rich 17B [22N] halo nucleus. The long tail manner is clearly shown in the results obtained of neutron and matter densities of these nuclei.  According to the calculated results it is found that this model provides a good description on the nuclear structure of above exotic nuclei. The reaction cross sections for these nuclei have been studied using the Glauber model with an optical limit approximation at high energy region.